PENGARUH KOMBINASI JENIS PELARUT DAN PERBANDINGANNYA TERHADAP KARAKTERISTIK EKSTRAK BUAH PANDAN (Pandanus tectorius) - Maya Isadora, Ni Kadek; Wartini, Ni Made; Semadi Antara, Nyoman (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2016)
Pandan plant (Pandanus  tectorius) grow well at the coast land of many tropical countries. The ripe fruit of the pandan plant has an oval shape, red color, and contain bioactive compounds, such as carotenoid. Extraction process is required to find the natural extract of the fruit. The aims of this study was to find out  the effect of the  solvent type combination  and  their ratio on  the characteristics of pandanus fruit extract. This study was experimental study, which was designed by randomized block design. The experiment was conducted as a factorial experiment, which consisted of two factors. The first factor was the  solvent  type  combination (acetone:chloroform and acetone:ethanol) and the second factor was  the ratio of solvent (1:1; 1:2; and 1:3). The  best solvent combination and its ratio for producing the extract was determined by effectiveness test. The results showed that the  solvent  type combination affected  the yield,  the  total carotenoids  content,  the level of brightness (L*), and the level of redness (a*) but  did not affect the level of yellowness (b*). The ratio of  solvent combination affected the yield but did not affect the total carotenoid content,  the level of brightness (L*), the level of redness (a*), and the level of yellowness (b*). The combination of acetone and ethanol with ratio of 1:3 was  the best  treatment to produce  pandanus  fruit extract with the yield of 3.13%;  total carotenoid content of 12.72%; the level of brightness (L*) 11.11; the level of redness (a*) 3.81; and the level of yellowness (b*) 31.48. Keywords: a combination of solvents, solvent ratio, pandanus tectorius, extraction
Keywords: 106